Virtual Reality in the Pediatric Intensive Care Unit: Patient Emotional and Physiologic Responses - Badke, Colleen M.; Krogh-Jespersen, Sheila; Flynn, Rachel M.; Shukla, Avani; Essner, Bonnie S.; Malakooti, Marcelo R. (Frontiers in Digital Health, 2022)
Context Patients in the Pediatric Intensive Care Unit (PICU) are limited in their ability to engage in developmentally typical activity. Long-term hospitalization, especially with minimal interpersonal engagement, is associated with risk for delirium and delayed recovery. Virtual reality (VR) has growing evidence as a safe, efficacious, and acceptable intervention for pain and distress management in the context of uncomfortable healthcare procedures, and for enhancing engagement in, and improving outcomes of rehabilitation therapy. Hypothesis Critically ill children may experience high levels of engagement and physiologic effects while engaging with VR. Methods and Models This cross-sectional study of 3–17-year-old children admitted to a PICU used a VR headset to deliver 360-degree immersive experiences. This study had a mixed-method approach, including standardized behavioral coding, participant and parent surveys, and participant physiologic responses. Investigators noted comments the child made about VR, observed emotional responses, and documented an engagement score. To determine physiologic response to VR, integer heart rate variability (HRVi) was collected 30 min before, during, and 30 min after VR. Results One hundred fifteen participants were enrolled from 6/18 to 10/19, and they interacted with VR for a median of 10 min (interquartile range 7–17). Most children enjoyed the experience; 83% of participants smiled and 36% laughed while using VR. Seventy-two percent made positive comments while using VR. The strongest age-related pattern regarding comments was that the youngest children were more likely to share the experience with others. Seventy-nine percent of participants were highly engaged with VR. Ninety-two percent of parents reported that VR calmed their child, and 78% of participants felt that VR was calming. HRVi Minimum scores were significantly higher during VR than pre- (p < 0.001) or post-VR (p < 0.001). There was no significant difference between pre-and post-VR (p = 0.387); therefore, children returned to their pre-intervention state following VR. Interpretations and Conclusions Children admitted to the PICU are highly engaged with and consistently enjoyed using VR. Both participants and parents found VR to be calming, consistent with intra-intervention physiologic improvements in HRVi. VR is an immersive tool that can augment the hospital environment for children.